Echinoids as hard substrates: varied examples from the Oligocene of Antigua, Lesser Antilles. Issue 3 (June 2017) - Donovan, Stephen K.; Harper, David A.T.; Portell, Roger W.; Toomey, James K.
Abstract: A collection of unremarkably preserved fossil irregular echinoids from the Upper Oligocene (Chattian) Antigua Formation of Antigua, Lesser Antilles, nonetheless provides evidence of a range of palaeoecological interactions. A dead test of the heart urchin Eupatagus sp. formed a hard substrate for the attachment of gregarious Thecidellina ? sp., a thecidoid brachiopod. Although obligate encrusters, these brachiopods more commonly occur as disarticulated valves free of the substrate in the Antillean fossil record. Elongate pits in test fragments were formed, variously, before and after the death of the host echinoids. These depressions on the external surface were formed either by invertebrates excavating domiciles or by claws or teeth; the echinoid later reclaimed the pits and grew new tubercles in the base. Post-mortem pits lack such new tuberculation. A test of Eupatagus sp. bears the boring Oichnus isp., formed either by a predator (gastropod?) or after the death of the echinoid (domicile), and a serpulid worm tube which grew on the test subsequent to the echinoid's death. The echinoid fauna of the Antigua Formation has been easy to collect and specimens are to be found in many museums; they now await re-examination to reveal palaeosynecological data analogous to that determined from the fragments discussed herein.